MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA GUNUNG PICUNG, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Kusumaningrum, Ria; Fauziah, Ratu Dinny; Nurhalim, Muhamad Wildan (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
Community service aims to sharia banking The subject of this community service is the Village Gunung Picung, Subdistric Pamijahan District/City Bogor, Province Jawa Barat In this community service, activities are carried out based on the following methods socialiszation and presentation The results of this community service are implementation of sharia bank recognition activities, With this community service, it can be concluded that activity has a good impacy on the community of Gunung Picung Village, especially business actors who need business capital.